Labour market flexibility, human resource management and corporate performance. - Michie, J; Sheehan-Quinn, M (Blackwell Publishing, 2001)
Labour market flexibility is often portrayed as a key to the competitive success of the UK and US economies. We surveyed several hundred firms in the UK, and using the resulting data (on over 200 manufacturing firms) this paper investigates the relationships between firms' use of flexible work practices, human resource systems and industrial relations on the one hand, and corporate performance on the other hand. The results suggest that 'low-road' practices – short-term contracts, a lack of employer commitment to job security, low levels of training and low levels of human resource sophistication – are negatively correlated with corporate performance. In contrast, it is found that 'high-road' work practices –'high commitment' organizations or 'transformed' workplaces – are positively correlated with good corporate performance. It is also found that human resource management practices are more likely to contribute to competitive success where they are introduced as a comprehensive package, or 'bundle' of practices. Significant interaction effects between human resource systems, trade unions and flexible work practices add further support to the bundling hypothesis.